Increasing Motivation among Language Learners through Individualized Assessment - Chalupa, Cynthia (Central European Journal of Educational Research, 2021)
An extensive body of research has shown that motivation is integral to successful and sustained language learning (Carreira, 2005; Cheng & Dornyei, 2007; Crookes & Schmidt, 1991; Dornyei, 1994; Ehrman, Leaver, & Oxford, 2003; Gardner, 2005; Matsumoto & Obana, 2001; Yang, 2008; Yu & Watkins, 2008). Maintaining student motivation in all aspects of language instruction, particularly assessment, can be challenging for multiple reasons, including learner differences, access to technology, and, most recently, reactions to pandemic learning. Instructors therefore face the challenge of creating assessments that not only evaluate students’ performance but also promote their ability and desire to learn. Based on the results of an action research project, this article highlights the benefits of two types of individualized assessment used to improve students’ motivation while evaluating their performance: work cycle projects and a course portfolio. Using qualitative data collected from student reflective statements, I argue, first, that the ability to choose assessment topics and types motivates students to focus closely on course content and work creatively; these choices ultimately improve their desire to learn course material more than traditional assessment types. Second, encouraging learners to utilize and reflect on their strengths using a portfolio as a form of assessment allows students to understand their strengths and weaknesses and empowers them as learners, thereby improving their motivation.